Estimation of power output from vertical jump: a comparison of three prediction equations - Musa, D. I.; Toriola, A. L. (Journal of Human Movement Studies, 2006)
The present study used the three Jump power equations in the literature on a sample of university students to determine if the results are comparable with those of previous studies utilising subjects of similar characteristics. The study also sought to determine the relationship between Jump peak power (PP) Output using the three equations and those estimated from the Wingate anaerobic test (WAnT). One hundred and sixteen male and female physical education (PE) students performed the vertical jump-and-reach test using the squat jump (SJ) protocol. Pearson's product moment correlation analysis was used to determine the relationship between the scores derived from the three power equations and those from WAnT, i.e., those of Sayers et al (1999), Harman et al (1991) and Lewis (Fox and Mathews, 1981). PP Output derived from Sayers et al's (1999) equation was greater than those derived from the other two equations, with that of Lewis "s equation producing the least PP Output. The relationship between the equation-predicted PP scores and the scores from WAnT was generally strong, but stronger in women than in men. It was concluded that the Sayers et al's equation is to be preferred in the assessment of jump peak power among PE students.